Genetic diversity of Ancylostoma ceylanicum and first molecular detection of Ancylostoma braziliense in stray dogs from Sarawak, Malaysia - Ahmad Syatir, Tahar; Sultana Parvin, Habeebur Rahman; Khatijah, Yaman; Romano, Ngui; Andrea Lim, Li Li; Josprin, Edwin; Nur Suhada, Saboden; Tracy, Manggi; Tan, Cheng Siang (Springer Nature Ltd, 2025)
Hookworms are blood-sucking intestinal parasites that can cause anaemia and protein loss in humans. Ancylostoma ceylanicum, a zoonotic hookworm species of dogs, is the second most common cause of human hookworm infections. With the increasing anthelmintic resistance risks and the uncontrolled stray dog population in Sarawak Borneo, East Malaysia, understanding the genetic structure of A. ceylanicum is crucial for tracking mutation patterns and assessing zoonotic transmission risks. This study determined the prevalence and genetic diversity of dog hookworm species using microscopy, PCR and sequencing, revealing A. ceylanicum (43.6%; 89/204), followed by mixed infections of A. ceylanicum and A. braziliense (9.3%; 19/204), single infections of A. caninum (6.3%; 13/204), and A. braziliense (1.4%; 3/204) in stray dogs in East Malaysia (Sarawak Borneo). Phylogenetic analysis of the cytochrome oxidase subunit 1 (COX1) gene showed that A. ceylanicum from Sarawak Borneo clustered across all major clades, indicating high genetic divergence and admixture. Haplotype analysis revealed that the Malaysian A. ceylanicum population highly mirrors those in Cambodia and Thailand, suggesting significant gene flow across Southeast Asia, while regional disparities exist compared to other countries. These findings provide critical epidemiological insights for hookworm control strategies, including stray dog management and potential adjustments to mass drug administration programs. The high genetic connectivity of A. ceylanicum population across borders underscores the need for enhanced surveillance, One Health approaches, and monitoring anthelminthic resistance to mitigate the risk of zoonotic transmission.